Data from: Health Canada’s use of accelerated review pathways and therapeutic innovation, 1995-2016: a cohort study - Lexchin, Joel (Dryad, 2018)
Objectives: This study examines the use of accelerated approval pathways
by Health Canada over the period 1995 to 2016 inclusive and the
relationship between the use of these pathways and the therapeutic gain
offered by new products. Design: Cohort study. Data sources: Therapeutic
Products Directorate, Biologics and Genetic Therapies Directorate, Notice
of Compliance database, Notice of Compliance with conditions web site,
Patented Medicine Prices Review Board, La revue Prescrire, World Health
Organization (WHO) Anatomical Therapeutic Chemical (ATC) classification
system. Interventions: None. Primary and secondary outcomes: Percent of
new drugs evaluated by Health Canada that went through an accelerated
pathway between 1995 and 2016 inclusive. Kappa values comparing the review
status to assessments of therapeutic value for individual drugs. Results:
438 (70.3%) drugs went through the standard pathway, 185 (29.7%) an
accelerated pathway. Therapeutic evaluations were available for 509 drugs.
Health Canada used an accelerated approval pathway for 159 of the 509
drugs whereas only 55 were judged to be therapeutically innovative. The
Kappa value for the entire period for all 509 drugs was 0.276 (95% CI
0.194, 0.359) or fair. Conclusion: Health Canada’s use of accelerated
approvals was stable over the entire time period. Its ability to predict
which drugs will offer a major therapeutic gain is relatively poor. The
findings in this study should provoke a discussion about whether Health
Canada should continue to use these pathways and if so how their use can
be improved.
Supplementary Table 2All drugs approved between 1995-2016 that did not
receive therapeutic assessmentsSupplementary Table 1All drugs approved
between 1995-2016 that received therapeutic assessments from Patented
Medicine Prices Review Board and/or La revue Prescrire